Immunoregulatory Monocyte Subset Promotes Metastasis Associated With Therapeutic Intervention for Primary Tumor - Shibuya, Takumi; Kamiyama, Asami; Sawada, Hirotaka; Kikuchi, Kenta; Maruyama, Mayu; Sawado, Rie; Ikeda, Naoki; Asano, Kenichi; Kurotaki, Daisuke; Tamura, Tomohiko; Yoneda, Atsuko; Imada, Keisuke; et al. (Frontiers in Immunology, 2021)
Systemic and local inflammation associated with therapeutic intervention of primary tumor occasionally promotes metastatic recurrence in mouse and human. However, it remains unclear what types of immune cells are involved in this process. Here, we found that the tissue-repair-promoting Ym1+Ly6Chi monocyte subset expanded as a result of systemic and local inflammation induced by intravenous injection of lipopolysaccharide or resection of primary tumor and promoted lung metastasis originating from circulating tumor cells (CTCs). Deletion of this subset suppressed metastasis induced by the inflammation. Furthermore, transfer of Ym1+Ly6Chi monocytes into naïve mice promoted lung metastasis in the mice. Ym1+Ly6Chi monocytes highly expressed matrix metalloproteinase-9 (MMP-9) and CXCR4. MMP-9 inhibitor and CXCR4 antagonist decreased Ym1+Ly6Chi-monocyte-promoted lung metastasis. These findings indicate that Ym1+Ly6Chi monocytes are therapeutic target cells for metastasis originating from CTCs associated with systemic and local inflammation. In addition, these findings provide a novel predictive cellular biomarker for metastatic recurrence after intervention for primary tumor.